Investigation of the influence of hyperthermia and soil Pollution with the petrochemicals on test objects using the Method of mathematical planning - Cherniak, Larysa; Petruk, Roman; Mikhieiev, Oleksandr; Madzhd, Svitlana; Petruk, Galyna (My University, 2022)
To increase the effi ciency of using methods for assessing the level of soil contamination by oil products against the background of the infl uence of other factors. Methodology. The authors consider the possibility of using bioassays to study the impact of several stressors on the test system. Based on the theory of experiment planning, a methodology for researching the infl uence of hyperthermia and soil contamination with kerosene on the growth parameters of test objects was developed. On the basis of the obtained experimental data, regression models were built which allow fi nding a numerical estimate of the impact of stress factors on changes in the characteristics of the test object. Findings. It was determined that, as a rule, in order to assess the infl uence of stressful factors when normalizing the assumed levels of their infl uence on humans and ecosystems using biotesting methods, such an assessment is carried out for individual factors. But, in the real conditions of existence of plants and organisms, they are exposed to the simultaneous infl uence of many factors that can interact non-additively, i.e. as antagonists or synergists. In order to increase the effi ciency of the use of methods for biotesting of the level of soil contamination by oil products against the background of the infl uence of other factors, the authors applied one of the methods of mathematical planning of the experiment. It was concluded that the eff ect of one factor depends, to a certain extent, on the eff ect of the other factor, the eff ect of which was studied in the work. The fact of the non-additive eff ect of the factors used in the experiment makes it possible to recommend the use of test objects in the practice of monitoring the condition of soils in technogenically loaded territories previously exposed to the action of hyperthermia. Originality. The toxic eff ect of the petroleum product depends, to a certain extent, on the eff ect of hyperthermia. Pretreatment of the test objects with a hyperthermic factor in a hormesis dose had a preventive eff ect, increasing the resistance of the test objects to the eff ect of the petroleum product. Practical value. The fact of the non-additive eff ect of the factors used in the experiment makes it possible to recommend the use of test objects previously exposed to the action of hyperthermia for monitoring the condition of soils in technogenically loaded territories.

Підвищення ефективності використання методів оцінки рівня забрудненості ґрунтів нафтопродуктами на фоні впливу інших факторів. Методика. Автори розглядають можливість використання біотестування для вивчення впливу кількох стресорів на тест-систему. На основі теорії планування експерименту розроблена методика дослідження впливу гіпертермії й забруднення ґрунту гасом на ростові параметри тест-об’єктів. На основі отриманих експериментальних даних побудовані регресійні моделі, що дозволяють знайти чисельну оцінку впливу стресових факторів на зміни характеристик тест-об’єкту. Результати. Визначено, що, як правило, для оцінки впливу дії стресуючих факторів при нормуванні припустимих рівнів їх впливу на людину та екосистеми з використанням методів біотестування така оцінка здійснюється для окремих факторів. Але в реальних умовах існування рослин та організмів вони піддаються одночасному впливу багатьох чинників, що можуть взаємодіяти неадитивно, тобто як антагоністи або синергісти. Авто рами, з метою підвищення ефективності використання методів біотестування рівня забрудненості ґрунтів нафтопродуктами на фоні впливу інших факторів, застосовано один із методів математичного планування експерименту. Зроблено висновок про те, що ефект від дії одного фактору в певній мірі залежить від дії іншого фактору, дію яких досліджували у роботі. Факт неадитивної дії наведених в експерименті факторів дає можливість рекомендувати застосовувати у практиці моніторингу стану ґрунтів на техногенно навантажених територіях попередньо підданих дії гіпертермії тест-об’єкти. Наукова новизна. Ефект від токсичної дії нафтопродукту в певній мірі залежить від дії гіпертермії. Попередня обробка тест-об’єктів гіпертермічним фактором у гормезисній дозі здійснила профілактичний вплив, підвищивши стійкість тест-об’єктів до дії нафтопродукту. Практична значимість. Факт неадитивної дії наведених в експерименті факторів дає можливість рекомендувати застосовувати попередньо піддані дії гіпертермії тест-об’єкти для моніторингу стану ґрунтів на техногенно навантажених територіях.
Keywords: mathematical planning; soil pollution; petrochemicals; математичне планування; забруднення грунтів; нафтопродукти; кафедра екології та екоменеджменту